Why Is the Corporate Tax Rate Lower than the Personal Tax Rate? - Clemens Fuest; Bernd Huber; Søren Bo Nielsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
In many OECD countries, statutory corporate tax rates are lower than personal income tax rates. The present paper argues that this tax rate differentiation is an optimal tax policy if there are problems of asymmetric information between investors and firms in the capital market. The reduction of the corporate tax rate below the personale tax rate encourages equity financing and thus mitigates the excessive use of debt financing induced by asymmetric information. Our main theoretical result stands in marked contrast to the traditional view of corporate taxation and corporate finance theory, according to which there is a tax disadvantage to equity financing. More recent empirical evidence on this issue, however, is in line with our result.
Keywords: 330